Hygiene, Sanitation and Potential Existence of Virulent Genes of E.coli in Lawar in Kuta: The Challenge for Tourism and Safe Food Provision in Bali - Ni Putu Eka Trisdayanti; Anak Agung Sagung Sawitri; I Nengah Sujaya (Universitas Udayana, 2015)
Background and purpose: The reoccurrence of food-borne parasitic outbreaks may be related to contamination by pathogenic strains of E.coli. As lawar (Balinese food) is a favorite of locals and tourists, there needs to be an examination into the presence of pathogenic strains of E.coli in lawar and its relation to hygiene and sanitation standards at food stalls in Kuta. Methods: Cross-sectional analytical study was conducted on 43 stalls that selling white lawar in North Kuta, Kuta and South Kuta. Observations and interviews to sellers were conducted to assess the personal hygiene practices, equipment/stall sanitation and sanitary facilities. Lawar samples were tested in the laboratory. Indicators of the food quality was the number of bacterial colonies with Total Plate Count (TPC), the presence of E.coli with fertilization techniques and the detection of E.coli virulence genes by PCR. Data were analyzed using univariate, bivariate and multivariate analysis. Results: As many as 44.2% of lawar contained bacterial colony >106 CFU/g; 46.5% of lawar positively contained E.coli, and 20% of those positive E.coli had the similar size band of Shiga Like Toxin Type I (SLT-I). The sellers with poor hygiene had higher risks of the presence of E.coli in the lawar compared with those having higher hygiene standards (adjusted OR=7.29; 95% CI 1.473-36.088). Conclusion: Lawar quality in Kuta was poor, as were hygiene practices and seller/stall sanitation.